2016
DOI: 10.3389/fphys.2016.00640
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Cortisol Administration; Effects on Risk Taking Behavior, Exercise Performance, and Physiological and Neurophysiological Responses

Abstract: Rationale: Exogenous cortisol is a modulator of behavior related to increased motivated decision making (Putman et al., 2010), where risky choices yield potentially big reward. Making risk based judgments has been shown to be important to athletes in optimizing pacing during endurance events (Renfree et al., 2014; Micklewright et al., 2015).Objectives: Therefore, the aims of this study were to examine the effect of 50 mg exogenous cortisol on neurophysiological responses and risk taking behavior in nine health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 59 publications
0
34
0
2
Order By: Relevance
“…The release of norepinephrine and epinephrine is also consistent with a psychophysiological stress response, which is in keeping with the anticipatory heart-rate rise [ 45 ] in HotH2H, whereas cortisol, which is also released in stressful situations, modulates behaviour related to increased motivated decision making, where high-risk choices yield potentially big rewards [ 46 ]. Exogenous cortisol supplementation increases risk-taking behaviour [ 47 ], which is associated with a higher initial pace [ 22 ]. Although speculative, these responses could account for the faster early pace in HotH2H.…”
Section: Discussionmentioning
confidence: 99%
“…The release of norepinephrine and epinephrine is also consistent with a psychophysiological stress response, which is in keeping with the anticipatory heart-rate rise [ 45 ] in HotH2H, whereas cortisol, which is also released in stressful situations, modulates behaviour related to increased motivated decision making, where high-risk choices yield potentially big rewards [ 46 ]. Exogenous cortisol supplementation increases risk-taking behaviour [ 47 ], which is associated with a higher initial pace [ 22 ]. Although speculative, these responses could account for the faster early pace in HotH2H.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 One study had a low RoB and investigated both short-term and long-term administration 23 The other study had a high RoB and investigated acute administration. 24…”
Section: Maximal Powermentioning
confidence: 99%
“…One study, which had a high RoB, found that POmax was lower in the group that received the acute administration of cortisol compared with placebo (P , 0.05). 24 Short-Term and Long-Term Administration…”
Section: Acute Administrationmentioning
confidence: 99%
“…Однократное введение АКТГ и глюкокортикоидов за 1-4 часа до начала упражнений не оказывало заметного влияния на физическую работоспособность, которая чаще всего оценивалась по времени отказа от работы при выполнении упражнений до изнеможения при беге или езде на велосипеде. Это было показано в работах с введением АКТГ 1-24 (Baume et al 2008;Soetens et al 1995), КЛ (Robertson et al 2016), гидрокортизона (Petrides et al 1997;Simunkova et al 2016), преднизолона (Arlettaz et al 2006;2008a), дексаметазона (Petrides et al 1994;.…”
Section: влияние глюкокортикоидов на физическую работоспособность человекаunclassified
“…Распространенное среди спортсменов мнение о положительном влиянии глюкокортикоидов на работоспособность, возможно, связано с изменением восприятия уровня нагрузки. Показано, что АКТГ 1-24 снимает чувство усталости при субмаксимальных нагрузках (Soetens et al 1995), а кортизол увеличивает рисковое поведение (Robertson et al 2016).…”
Section: влияние глюкокортикоидов на физическую работоспособность человекаunclassified